Application of Maxwell-Wagner Polarization in Delay Lines - Prodromakis,T; Papavassiliou,C; Toumazou,C (Microelectronics Journal, 2010)
The propagation characteristics of metal–insulator–semiconductor (MIS) lines are controlled by the resistivity of the substrate, the operating frequency and the ratio of the semiconductor to insulator layer thicknesses. A strong interfacial polarisation, also known as the Maxwell–Wagner polarisation, is often responsible for the significant slow-down of the propagation velocity of MIS microstrip transmission lines. This phenomenon has been applied in the development of miniature delay lines exhibiting large electrical dimensions. In this paper we review most previously presented designs and we examine the effect of this polarization mechanism under various parameters. Finally, the presented micro-scale delay lines, exhibit comparable slowing factors with our predecessors at the cost of lower attenuation.